Analysis of the expression of putative heat-stress related genes in relation to thermotolerance of cork oak - Correia, Barbara; Rodriguez, José Luis; Valledor, Luis; Almeida, Tânia; Santos, Conceição; Cañal, Maria Jesus; Pinto, Glória (Journal of Plant Physiology, 2014)
Cork oak (Quercus suber L.) is a research priority in the Mediterranean area and because of cork oaks’ dis- tribution these stands are experiencing daily stress. Based on projections of intensifying climate change and considering the key role of exploring the recovery abilities, cork oak seedlings were subjected to a cumulative temperature increase from 25◦C to 55◦C and subsequent recovery. CO2 assimilation rate, chlorophyll fluorescence, anthocyanins, proline and lipid peroxidation were used to evaluate plant per- formance, while the relative abundance of seven genes encoding for proteins of cork oak with a putative role in thermal/stress regulation (POX1, POX2, HSP10.4, HSP17a.22, CHS, MTL and RBC) was analyzed by qPCR (quantitative Polymerase Chain Reaction). A temperature change to 35◦C showed abundance alterations in the tested genes; at 45◦C, the molecular changes were associated with an antioxidant response, possibly modulated by anthocyanins. At 55◦C, HSP17a.22, MTL and proline accumulation were evident. After recovery, physiological balance was restored, whereas POX1, HSP10.4 and MTL abundances were suggested to be involved in increased thermotolerance. The data presented here are expected to pinpoint some pathways changes occurring during such stress and further recovery in this particular Mediterranean species. ©
Keywords: high temperature; Plant performance; Quercus suber; Recovery

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Soil organic matter quality and microbial catabolic functions along a gradient of wildfire history in a Mediterranean ecosystem - Guénon, René; Vennetier, Michel; Dupuy, Nathalie; Ziarelli, Fabio; Gros, Raphaël (Applied Soil Ecology, 2011)
The principal aim of this research was to determine the inﬂuence of an increasing wildﬁre history on the recovery at short and long term of soil organic matter (SOM) composition and microbial properties. The contemporary wildﬁre events (since 1950) were recorded for 27 plots located on the siliceous part of the French Mediterranean region (Maures mountain ranges). A wildﬁre history index was built, tested and calculated in order to display numerical values representative of the different wildﬁre history parameters (i.e. number of ﬁres, time since ﬁre and mean ﬁre interval). Microbial basal respiration and biomass were analysed as well as intensity of the use of 31 C-substrates, catabolic diversity and C-substrates utilisation proﬁles. Furthermore, a qualitative characterisation of the SOM was carried out by solid state 13 C NMR. Potential drivers of the microbial recovery were identiﬁed by studying the relationships between microbial activities and chemical functions of SOM. Our results showed that ﬁre histories resulting in considerable losses or alterations of SOM, such as recent or close ﬁres, decreased the microbial catabolic evenness. This could be attributed to a preferential utilisation of N-containing compounds and complex substrates such as aromatic and polymers reﬂecting a greater N microbial demand and a selection of speciﬁc catabolic functions. Moreover, a large number of ﬁres (4 ﬁres in 57 years compared to 1–2) resulted in lasting degradation of the relative intensity of methyl C function in polymethylene, O-Alkyl C, aromatic C and phenolic C functions inducing a slow-down in recovery of microbial properties. These results also conﬁrm our hypothesis that some chemical functions of SOM can be in equilibrium with wildﬁre history. Finally, this research demonstrates that FT-NIR analysis can be used as a valuable tool to assess both the wildﬁre history and the vulnerability of soil quality to shifts in historical ﬁre regimes
Keywords: 13C NMR; Biolog; Catabolic evenness; Fire recurrence; FT-NIR spectroscopy; Recovery

Drought-induced photosynthetic inhibition and autumn recovery in two Mediterranean oak species (Quercus ilex and Quercus suber) - Vaz, M; Pereira, J S; Gazarini, L C; David, T S; David, J S; Rodrigues, A; MAROCO, J; Chaves, M M (Tree Physiology, 2010)
Responses of leaf water relations and photosynthesis to summer drought and autumn rewetting were studied in two evergreen Mediterranean oak species, Quercus ilex spp. rotundifolia and Quercus suber. The predawn leaf water potential (ΨlPD), stomatal conductance (gs) and photosynthetic rate (A) at ambient conditions were measured seasonally over a 3-year period. We also measured the photosynthetic response to light and to intercellular CO2 (A/PPFD and A/Ci response curves) under water stress (summer) and after recovery due to autumn rainfall. Photosynthetic parameters, Vcmax, Jmax and triose phosphate utilization (TPU) rate, were estimated using the Farquhar model. RuBisCo activity, leaf chlorophyll, leaf nitrogen concentration and leaf carbohydrate concentration were also measured. All measurements were performed in the spring leaves of the current year. In both species, the predawn leaf water potential, stomatal conductance and photosynthetic rate peaked in spring, progressively declined throughout the summer and recovered upon autumn rainfall. During the drought period, Q. ilex maintained a higher predawn leaf water potential and stomatal conductance than Q. suber. During this period, we found that photosynthesis was not only limited by stomatal closure, but was also downregulated as a consequence of a decrease in the maximum carboxylation rate (Vcmax) and the light-saturated rate of photosynthetic electron transport (Jmax) in both species. The Vcmax and Jmax increased after the first autumnal rains and this increase was related to RuBisCo activity, leaf nitrogen concentration and chlorophyll concentration. In addition, an increase in the TPU rate and in soluble leaf sugar concentration was observed in this period. The results obtained indicate a high resilience of the photosynthetic apparatus to summer drought as well as good recovery in the following autumn rains of these evergreen oak species.
10.1093/treephys/tpq044
Keywords: biochemical parameters; Drought; Mediterranean; photosynthesis; Quercus ilex; Quercus suber; Recovery; water relations